Field line distribution of mass density at geostationary orbit. Issue 6 (4th June 2015) - Denton, R. E.; Takahashi, Kazue; Lee, Jimyoung; Zeitler, C. K.; Wimer, N. T.; Litscher, L. E.; Singer, H. J.; Min, Kyungguk
Abstract The distribution of mass density along the field lines affects the ratios of toroidal (azimuthally oscillating) Alfvén frequencies, and given the ratios of these frequencies, we can get information about that distribution. Here we assume the commonly used power law form for the field line distribution, ρm = ρm, eq(LRE/R)α, where ρm, eq is the value of the mass density ρm at the magnetic equator, L is the L shell, RE is the Earth's radius, R is the geocentric distance to a point on the field line, and α is the power law coefficient. Positive values of α indicate that ρm increases away from the magnetic equator, zero value indicates that ρm is constant along the magnetic field line, and negative α indicates that there is a local peak in ρm at the magnetic equator. Using 12 years of observations of toroidal Alfvén frequencies by the Geostationary Operational Environmental Satellites, we study the typical dependence of inferred values of α on the magnetic local time (MLT), the phase of the solar cycle as specified by the F10.7 extreme ultraviolet solar flux, and geomagnetic activity as specified by the auroral electrojet (AE) index. Over the mostly dayside range of the observations, we find that α decreases with respect to increasing MLT and F10.7, but increases with respect to increasing AE. We develop a formula that depends on all three parameters, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj22dcd18p" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α3Dmodel=2.2+1.3·cosMLT·15∘+0.0026·AE·cos(MLT−0.8)·15∘+2.1·10−5·AE·F10.7−0.010·F10.7</alternatives>, that models the binned values of α within a standard deviation of 0.3. While we do not yet have a complete theoretical understanding of why α should depend on these parameters in such a way, we do make some observations and speculations about the causes. At least part of the dependence is related to that of ρm, eq; higher α, corresponding to steeper variation with respect to magnetic latitude, occurs when ρm, eq is lower.